Improved near-infrared methane band models and k-distribution parameters from 2000 to 9500 cm(-1) and implications for interpretation of outer planet spectra - Irwin, P; Sromovsky, L; Strong, E; Sihra, K; Teanby, N; Bowles, N; Calcutt, S; Remedios, J (2006)
The band model fits of Sihra [1998. Ph.D. Thesis. University of Oxford], subsequently reported by Irwin et al. [2005. Icarus 176, 255-271], to new measurements of low-temperature near-infrared self-broadened methane absorption spectra combined with earlier warmer, longer path measurements of both self- and hydrogen-broadened methane spectra measured by Strong et al. [1993. J. Quant. Spectrosc. Radiat. Transfer 50, 363-429], have been found to contain severe artefacts at wavelengths of very low methane absorption. Although spectra calculated from these new band data appear to be reliable for paths with low to medium absorption, transmissions calculated for long paths of high methane absorption, such as for Uranus, Neptune and Titan are severely compromised. The recorded laboratory transmission spectra of Sihra [1998. Ph.D. Thesis. University of Oxford] and Strong et al. [1993. J. Quant. Spectrosc. Radiat. Transfer 50, 363-429] have thus been refitted with a more robust model and new k-distribution data for both self- and hydrogen-broadened methane absorption derived. In addition, a new model of the temperature dependence of the absorption has been employed that improves the quality of the fit and should also provide more accurate extrapolations to low temperatures. © 2005 Elsevier Inc. All rights reserved.